LOX-1 gene variants and maternal levels of plasma oxidized LDL and malondialdehyde in patients with gestational diabetes mellitus - Aydemir, Birsen; Baykara, Onur; Cinemre, Fatma Behice Serinkan; Cinemre, Hakan; Tuten, Abdullah; Kiziler, Ali Riza; Akdemir, Nermin; Oncul, Mahmut; Kaya, Baris; Sozer, Volkan; Erkorkmaz, Unal; Uzun, Hafize (SPRINGER HEIDELBERG, 2016)
Purpose The aim of this study was to investigate the relationships between the maternal levels of oxidized LDL (ox-LDL), lipid peroxidation marker malondialdehyde (MDA) and LOX-1 3'UTR188C/T and K167N single nucleotide polymorphisms in pregnant Turkish women with gestational diabetes mellitus (GDM). Methods 116 pregnant women with GDM and 120 healthy pregnant women from the same geographic region were included in the study. Polymerase chain reaction-based restriction analysis was used to identify 3'UTR188C/T and K167N polymorphisms of the LOX-1 gene. Plasma ox-LDL and MDA levels were determined by enzyme-linked immunosorbent assay and spectrophotometric method in all study subjects, respectively. Results Our results indicated that the distribution of the LOX-1 3'UTR188C/T and K167N genotypes and alleles did not differ significantly among subjects with or without GDM (p> 0.05). TT and NN genotype carriers are associated with some glucose metabolism parameters (p 0.05). According to the combined genotype analysis of LOX-1 3'UTR 188 TT and K167N NN polymorphisms, plasma MDA and ox-LDL levels were significantly different between women with GDM and healthy subjects either with or without combined TT/NN genotype carriers (p< 0.001). Conclusions According to our results, ox-LDL and MDA levels were increased in GDM pregnant women and healthy pregnant women either with or without combined TT/NN genotype carriers, for our Turkish sample, these genotype carriers appear to be related with increased oxidative stress in patients with GDM.
Keywords: Gestational diabetes mellitus; Oxidized LDL; Malondialdehyde; Lectin-like oxidized LDL receptor-1 gene polymorphism; LOW-DENSITY-LIPOPROTEIN; HUMAN LECTIN-LIKE; OLR1 GENE; RECEPTOR-1; POLYMORPHISM; ASSOCIATION; EXPRESSION; RISK; ADHESION; BINDING; Obstetrics & Gynecology